Theoretical Prediction of Ultrasonic Velocity in Organic Liquid Mixtures - R. Uvarani; S. Punitha (E-Journal of Chemistry)
Theoretical values of ultrasonic velocity in the binary mixtures of cyclohexanone with 2-propanol and 2-methyl-2-propanol have been evaluated at 303 K using Nomoto’s relation, collision factor theory, free length theory, ideal mixture relation, Junjie’s method. Theoretical values are compared with the experimental values and the validity of the theories are checked by applying the chi-square test for goodness of fit and by calculating the average percentage error (APE).